Antiplatelet Activity of Isorhamnetin via Mitochondrial Regulation - Lyanne Rodríguez; Lina Badimon; Diego Méndez; Teresa Padró; Gemma Vilahur; Esther Peña; Basilio Carrasco; Hermine Vogel; Iván Palomo; Eduardo Fuentes (MDPI AG, 2021)
With the diet, we ingest nutrients capable of modulating platelet function, which plays a crucial role in developing cardiovascular events, one of the leading causes of mortality worldwide. Studies that demonstrate the antiplatelet and antithrombotic potential of bioactive compounds are vital to maintaining good cardiovascular health. In this work, we evaluate the flavonol isorhamnetin's antiplatelet effect on human platelets, using collagen, thrombin receptor activator peptide 6 (TRAP-6), and phorbol myristate acetate (PMA) as agonists. Isorhamnetin induced a significant inhibition on collagen- and TRAP-6-induced platelet aggregation, with half-maximum inhibitory concentration (IC50) values of 8.1 ± 2.6 and 16.1 ± 11.1 µM, respectively; while it did not show cytotoxic effect. Isorhamnetin reduced adenosine triphosphate levels (ATP) in platelets stimulated by collagen and TRAP-6. We also evidenced that isorhamnetin's antiplatelet activity was related to the inhibition of mitochondrial function without effect on reactive oxygen species (ROS) levels. Additionally, we investigated isorhamnetin's effect on thrombus formation in vitro under flow conditions on the damaged vessel wall. In this context, we demonstrate that isorhamnetin at 20 µM induced a significant inhibition on platelet deposition, confirming its antithrombotic effect. Our findings corroborate the antiplatelet and antithrombotic potential of isorhamnetin present in many foods of daily consumption.